Inhibitions in speaking during cross-cultural exchange projects and how they may affect intercultural learning at university courses - STOROZENKO, VICTORIA; SCHMIDT-BERNHARDT, ANGELA; ADAMCZAK-KRYSZTOFOWICZ, SYLWIA (Glottodidactica, 2017)
Inhibitions in speaking (or fear of speaking) can affect communicative processes in cross-cultural groups of learners. They may result from numerous emotional, cognitive or psychophysiological factors. The article concentrates on the most common types of inhibitions observed in a group of students during a project based seminar which took place in Poznań in December 2016. The seminar was a joint venture organised by Adam Mickiewicz University in Poznań and the University of Marburg. The student participants were working on developing cultural teaching materials, and after the seminar they took part in a qualitative survey intended to examine their reflections concerning the project. The article presents a discussion of selected findings.